(3ebOeI ddJbfjGJ GdeYGUQI aj YUQ GdeYdheGJ (B/s - (3gGcGQ, ejTjds; (3HGQOf, QhHQJ s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2006)
(3GdJbfjI aj GdYGde GdeJZjQ(B, (3ehGQO GdJbfjI(B, (3Md GdeTcdI h GdfXe(B, (3YUQ GdMGSH GdGdcJQhfj(B, (3fXe GdGJUGdGJ(B, (3GJUGdGJ GdQSheGJ(B, (3GdGJUGdGJ GdGdcJQhfjI(B, (3JTZjd GdehGO(B- (3GdJUfjY(B- (3GdJTjjO(B- (3HfGA Gdgjcd(B-(3GOGQI fXe GdGfJGL (B- (3GdWGbI(B- (3GdbhI h Gdfbd hGNjQG GdJGKjQGJ GdMGdjI h GdeSJbHdjI(B.s
Keywords: (3JbfjGJ eYGUQIs; (3YUQ GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s